Proceedings of the 18th International Workshop on Mobile Computing Systems and Applications 2017
DOI: 10.1145/3032970.3032983
|View full text |Cite
|
Sign up to set email alerts
|

A Practical GPS Location Spoofing Attack in Road Navigation Scenario

Abstract: High value of GPS location information and easy availability of portable GPS signal spoofing devices incentivize attackers to launch GPS spoofing attacks against location-based applications. In this paper, we propose an attack model in road navigation scenario, and develop a complete framework to analyze, simulate and evaluate the spoofing attacks under practical constraints. To launch an attack, the framework first constructs a road network, and then searches for an attack route that smoothly diverts a victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 6 publications
(13 reference statements)
0
44
0
Order By: Relevance
“…Another attack against integrity that has been shown to be successful is Global Positioning System (GPS) spoofing [62]. In GPS spoofing, attackers broadcast false GPS signals in order to cause travelers to change their routes based on the corrupt/malicious data.…”
Section: Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Another attack against integrity that has been shown to be successful is Global Positioning System (GPS) spoofing [62]. In GPS spoofing, attackers broadcast false GPS signals in order to cause travelers to change their routes based on the corrupt/malicious data.…”
Section: Integritymentioning
confidence: 99%
“…can be attacked [32]. Additionally, more complex systems such as infotainment systems with GPS for on-board navigation may be targeted by attackers as shown in [62]. Exfiltration of data from on-board sensors and systems may lead to the exposure of privacy issues as well.…”
Section: Attack Surface Analysis Of Itsmentioning
confidence: 99%
“…The problem of GNSS spoofing attacks should be thoroughly considered as serious threat for GNSSbased applications in maritime sector. Research groups have already demonstrated successful GPS spoofing attacks in air (Kerns et al, 2014), maritime (Bhatti, and Humphreys, 2017), and land (Zeng et al, 2017) navigation applications. Maritime sector relies increasingly on information and communication technologies, with numerous operational procedures under development and data management not always considered a critical element of sustainable development and operations.…”
Section: Gnss Spoofing In Maritime Sectormentioning
confidence: 99%
“…One of the main reasons is the lack of any form of signal authentication. It is today possible to change the course of a ship [11], force a drone to land in an hostile area [12] or fake the current location in a road navigation system [13] by simply spoofing GPS signals. The increasing availability of low-cost radio hardware platforms make it feasible to execute such attacks with less than few hundred dollars worth of hardware equipment.…”
Section: Introductionmentioning
confidence: 99%
“…e ∈ V such that (s, e) ∈ E do13 if e ∈ v and F ilter(s, e, p) passed then 14 p.score ← p.score * Score(s, e, p)15 GenerateSpoofedPaths (e, d)16 end ← p − [s] 18 v ← v − {s}Algorithm 1: Spoofed Paths Algorithm world along with various meta-data such as types of roads and buildings. Each geographic area can be represented as G = (A, C, θ, ϑ), where A is a set of atomic sections and C = {χ = (s, s )|s, s ∈ A} is a set of connections where χ indicates a connection between two atomic sections s and s .…”
mentioning
confidence: 99%